Frontal Horn of Lateral Ventricle of Brain and Its Relation with Age, Gender and Side: Morphometric Study by Computed Tomography among Bangladeshi Population (IAHS Medical Journal, 2024)
Background: Knowledge of the baseline reference value of frontal horn size is necessary for the initial and precise analysis of ventriculomegaly. The purpose of this study was to determine the size of frontal horn of lateral ventricle and its relation with age, gender and side among adult Bangladeshi population of Chattogram district.Materials and methods: This cross-sectional analytical study was conducted during the period from July 2022 to June 2023 in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 150 respondents of 20-60 years who had normal Computed Tomography (CT) scans as reported by an expert radiologist. For statistical analysis, Mann-Whitney U test, Wilcoxon signed rank test and ANOVA test were done. p-value was considered significant if it was